Activity-Based Costing System Dalam Penetapan Harga Pokok Produksi Serta Pengaruhnya Terhadap Kinerja Perusahaan (Studi Kasus Industri Kain Tenun Ikat Medali Mas Di Kota Kediri) - Kusumaningtyas, Dian; Izzatul, Rilla (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2017)
Kediri has Tenun Ikat centers so that people have opportunities to improve their standard of living through weaving industry . In the embodiment , the necessary foundation of the formation of a strong organization in the industry SMEs, especially craftsman weaving Medal Mas Kediri on managerial human resources, marketing , production and managerial finance in preparing business continuity in the long-term direction . Method cost of product is defined as a way to take into account the elements of cost into the cost of production . In the process of calculating all elements of cost into the cost of production of the many businesses went a different way. The concept of Activity Based Costing or ABC method is an alternative to overhead cost. Based on the background that has been described so obtained formulation of the problem " Is there a difference between traditional calculation with activity based costing system in determining the cost of production , sales price , profitability and the implementation of the company's performance . The results of this study are expected to provide feedback or to provide benefits to industry weaving craft in use calculation of the cost of production , sales price , profitability and its implementation on the company's performance , as well as add insight to the reader and can be used for further research. Calculation of the cost of production by using the traditional calculation . Rp . 130,453.67 while using ABC Rp 136 411 , 46. When compared with the profit earned by the traditional calculation of Rp . 29546.33 while the ABC Rp . 23588.54 . For higher profit calculation using the traditional cost allocation caused many not included in the BOP . Special for woven product manufacturers can not sell the goods in accordance with the expected profit due to market price in accordance with the type of product and quality of raw materials used .